Self-repairing radix-2 signed-digit adder with multiple error detection, correction, and fault localization. (August 2016) - Moradian, Hossein; Lee, Jeong-A; Hashmi, Adnan
Abstract: The advent of advanced microelectronic technologies and scale downing into nanometer dimensions has made current digital systems more susceptible to faults and increases the demand for reliable and high-performance computing. Current solutions have so far used the parity prediction scheme to increase reliability and detect fault in adder modules, but they add perceptible area overhead to the circuit. In this paper, we present two new efficient methods for fault detection and localization, in addition to the full error-correction, targeting stack-at and multi-cycle transient (MCT) faults in radix-2 signed-digit adders through a combination of time and hardware redundancy. In this study, we use the self-checking full adder that can identify a fault based on internal functionality to detect any fault in the adder modules. The detection of a fault is followed by input inversion, recomputation, and appropriate output inversion to correct the error and localize the fault. The error-correction method employs fault masking by utilizing the self-dual concept, which is based on the fact that in the presence of a fault, the designed technique results in a fault-free complement of the expected output when fed by the complement of its input operands. In addition, the existence of any fault in the input lines of the adder modules can be identified by low-cost parity checking error-detection approach, and a faulty module can be localized by comparing the faulty output from the first computation with the fault-free output from the recomputation. Based on the experimental results, the area occupied by our designs is approximately 50% that of the area used by previous designs that employ the parity prediction scheme. In addition to the area reduction, our design approaches result in a higher reliability with less power consumption and low time delay. Highlights: Two self-checking BSDN adders with multiple fault detection, localization and correction capability Proposed methods targeting stack-at and multi-cycle transient (MCT) faults The error-correction method employs fault masking by utilizing the self-dual concept. Designed approaches result in higher reliability with low overhead in area, power, and time delay.